2018
DOI: 10.3892/etm.2018.5801
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA gene polymorphism and cutaneous adverse reactions caused by antiepileptic drugs

Abstract: The association between cutaneous adverse drug reactions (cADRs) caused by antiepileptic drugs (AEDs) and human leukocyte antigen-A (HLA-A) and HLA-B genes in Chinese Han population in Shanghai was investigated. Through the case-control study, 30 child patients with AED-induced cADRs (cADRs group), 60 AED-tolerant child patients (AED-tolerant group) and 60 normal children not taking AEDs (normal group) were collected. The HLA-B*15:02 and HLA-A*31:01 genotypes were detected using the polymerase chain reaction-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…Therefore, it is not possible to state the difference in carrier frequency between the control population and CAR+ patients is due to sensitivity to these drugs. Although previous studies with smaller samples of tolerant and sensitive individuals in other populations found an association between the HLA‐A*31:01 allele and ASM‐induced CAR, the absence in our study, despite the sample size, of any differences when tolerant and sensitive patients were compared suggests that other variables may play a role in this difference 26–30 . Hence, future studies should investigate whether another variable can explain the strong difference between sensitive patients and control subjects and the absence of any difference between sensitive and tolerant patients.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Therefore, it is not possible to state the difference in carrier frequency between the control population and CAR+ patients is due to sensitivity to these drugs. Although previous studies with smaller samples of tolerant and sensitive individuals in other populations found an association between the HLA‐A*31:01 allele and ASM‐induced CAR, the absence in our study, despite the sample size, of any differences when tolerant and sensitive patients were compared suggests that other variables may play a role in this difference 26–30 . Hence, future studies should investigate whether another variable can explain the strong difference between sensitive patients and control subjects and the absence of any difference between sensitive and tolerant patients.…”
Section: Discussioncontrasting
confidence: 67%
“…Although previous studies with smaller samples of tolerant and sensitive individuals in other populations found an association between the HLA-A*31:01 allele and ASM-induced CAR, the absence in our study, despite the sample size, of any differences when tolerant and sensitive patients were compared suggests that other variables may play a role in this difference. [26][27][28][29][30] Hence, future studies should investigate whether another variable can explain the strong difference between sensitive patients and control subjects and the absence of any difference between sensitive and tolerant patients. We do not have enough evidence to indicate screening for this allele to prevent CAR among Brazilian patients even though it has a high prevalence in our population (9%).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that discussed and researched genetic susceptibility to SCARs showed higher susceptibility in Thai and Chinese populations due to specific Human Leukocyte Antigens (HLAs), [45][46][47][48][49] and that might explain why Thailand and China ranked first and second in the number of reports.…”
Section: Discussionmentioning
confidence: 99%